Population-based incidence and outcomes of acute aortic dissection in Japan. Issue 7 (30th June 2021) - Yamaguchi, Tetsuo; Nakai, Michikazu; Yano, Takao; Matsuyama, Masakazu; Yoshino, Hideaki; Miyamoto, Yoshihiro; Sumita, Yoko; Matsuda, Hitoshi; Inoue, Yousuke; Okita, Yutaka; Minatoya, Kenji; Ueda, Yuichi; et al.
Abstract: Aims: The population-based incidence and outcomes of acute aortic dissection (AAD) are still unknown because some patients are already dead on arrival, and the accurate diagnosis of AAD is difficult due to the low autopsy rate. We performed a population-based review of all patients with AAD in a well-defined geographical area in Japan between 2016 and 2018. Methods and results: Data of all patients with AAD at Miyazaki Prefectural Nobeoka Hospital (MPNH), which performs medical care for 120 000 residents, were collected retrospectively. The emergency medical service is dedicated to the transfer of all patients in this area to the MPNH. For all patients who were dead on arrival, the diagnosis of AAD was made by autopsy imaging (AI) using computed tomography. The age-adjusted incidence and mortality per 100 000 population were calculated using the Japanese population distribution model in 2015. The total incidence of AAD was 79 (type A: 64.5%, n = 51). Of those, 60.8% (31/51) of patients with type A and 21.4% (6/28) with type B were dead on arrival and diagnosed by AI. The 30-day mortality rates were 74.5% (38/51) in type A and 25.0% (7/28) in type B. The age-adjusted incidence and mortality of AAD per 100 000 inhabitants were 17.6 (type A: 11.3, type B: 6.2) and 9.9 (type A: 8.4, type B: 1.5), respectively. Conclusions: The population-based survey of AAD showed that the age-adjusted incidence of AAD was two-fold higher than in previous reports, and the actual mortality rates were markedly higher due to the high incidence of dead-on-arrival. Graphical Abstract: